2003
DOI: 10.1002/ajpa.10399
|View full text |Cite
|
Sign up to set email alerts
|

Natural history ofHomo erectus

Abstract: Our view of H. erectus is vastly different today than when Pithecanthropus erectus was described in 1894. Since its synonimization into Homo, views of the species and its distribution have varied from a single, widely dispersed, polytypic species ultimately ancestral to all later Homo, to a derived, regional isolate ultimately marginal to later hominin evolution. A revised chronostratigraphic framework and recent work bearing either directly or indirectly on reconstructions of life-history patterns are reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
154
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(177 citation statements)
references
References 225 publications
5
154
1
7
Order By: Relevance
“…The discussion on the classification of the Dmanisi material is testimony to the diversity of opinions (cf. Gabunia et al, 2002;Antó n, 2003;Schwartz and Tattersall, 2005;Rightmire et al, 2006). In Schwartz and Tattersall's view: 'at the morphrecognition level none of its constituents can at present be shown to bear a compelling resemblance to claimed Homo erectus materials from either Africa or Asia, despite a few isolated similarities here or there.…”
Section: Introductionmentioning
confidence: 96%
“…The discussion on the classification of the Dmanisi material is testimony to the diversity of opinions (cf. Gabunia et al, 2002;Antó n, 2003;Schwartz and Tattersall, 2005;Rightmire et al, 2006). In Schwartz and Tattersall's view: 'at the morphrecognition level none of its constituents can at present be shown to bear a compelling resemblance to claimed Homo erectus materials from either Africa or Asia, despite a few isolated similarities here or there.…”
Section: Introductionmentioning
confidence: 96%
“…With the emergence of the genus Homo at 2.0 mya (H. ergaster/erectus) [4], there was a marked increase in body size, mainly in females, who almost double in size compared with Australopithecine [5]. The oldest fossil evidence for Homo sapiens is from Southern and Eastern Africa, dating to about 160-250 kya [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Higher variation in the early Indonesian record was also documented by Antón ( , 2003 and Kaifu et al (2008). One possibility is that some of the individual differences in the early part of the record are enhanced by taphonomic processes as all of the Sangiran fossils evaluated here have cracks running throughout, some were substantially reconstructed (Skull IX), and, in the case of Sang 4, the two pieces of the posterior vault are not attached.…”
Section: Variation Within Indonesian Subsamplesmentioning
confidence: 71%
“…There is substantial variation within this sample that spans three continents and more than a million years of evolutionary change. Some of this variation is attributable to diachronic change (Wolpoff et al, 1994;Antón, 2003;Kaifu et al, 2005Kaifu et al, , 2008, and to geography (perhaps related to genetic drift or local adaptation) Kidder and Durband, 2004;Durband, 2006;Baab, 2010), but is also influenced by cranial size (Santa Luca, 1980;Antón et al, 2007;Baab, 2008b;Kaifu et al, 2008). Some studies have found that the Zhoukoudian hominins are particularly distinct in their craniometric dimensions Kidder and Durband, 2004), while others have indicated that the Ngandong/Sambungmacan/Ngawi series of calvaria are at least as distinct (Baab, 2010;Zeitoun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%